Pygmalion National Silver Award - Mouzouropoulos, Theseas (My University, 2026)
The award was received by the Creative Club of Cyprus member of the Art Directors Club of Europe (ADCE). The Semiotics & Visual Communication Lab (www.svclab.com) was commissioned by the Water Board of Limassol to design the company's annual report. As a member of the SVC Lab we were involved in the design process and production of the biennial report under the supervision of Evripides Zantides.
Keywords: Arts and entertainment